2019
DOI: 10.1007/s00428-019-02586-w
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic reporting increases quality of upper gastrointestinal cancer pathology reports

Abstract: Introduction Traditionally, surgical pathology reports are narrative. These report types are prone to error and missing data; therefore, structured standardized reporting was introduced. However, the effect of synoptic reporting on the completeness of esophageal and gastric carcinoma pathology reports is not yet established. Materials and methods A population-based retrospective nationwide cohort study in the Netherlands was conducted over a period of 2012–2016, utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…The usage of synoptic reporting reduced time for documentation of examination results compared to traditional narrative reporting, which is in line with previous studies [32]. Potential reasons include the reduced effort for text formatting [32,33], correction of dictation errors (casus, numerus, and genus of word endings) [33], use of defaults (normal finding), automated calculations (prostate volume and tumor volumes in biopsies), proofreading for completeness, and consistency of the report [11,13,14]. The comparison of time savings between diagnostic departments showed greater time savings for radiology compared to pathology.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The usage of synoptic reporting reduced time for documentation of examination results compared to traditional narrative reporting, which is in line with previous studies [32]. Potential reasons include the reduced effort for text formatting [32,33], correction of dictation errors (casus, numerus, and genus of word endings) [33], use of defaults (normal finding), automated calculations (prostate volume and tumor volumes in biopsies), proofreading for completeness, and consistency of the report [11,13,14]. The comparison of time savings between diagnostic departments showed greater time savings for radiology compared to pathology.…”
Section: Discussionsupporting
confidence: 72%
“…This way of documentation is suitable for different purposes like medical history, radiological, and histological examinations, and it has already been shown that such reports are more accurate, clearer, and coherent than narrative reports [10]. The broadest application of synoptic reporting is currently in oncologic pathology [11][12][13][14][15][16], radiology [17,18], and operative reports in surgery [19,20]. An essential prerequisite for the successful expansion of this reporting method is the development of international standards based on the best available evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, SR has been implemented in more than 31 different protocols, all of which have been formally approved by the Dutch Society of Pathology. Although the benefits of SR for Dutch patients has been investigated in a few types of cancer (e.g., colorectal [35,42], gallbladder [43]), this has not been done in prostate cancer.…”
Section: Synoptic Reportingmentioning
confidence: 99%
“…A complete and accurate pathology report is crucial to diagnostic workup, therapeutic management, and posttherapeutic follow-up of every cancer patient. Baranov et al 83 analyzed more than 1000 narrative and synoptic (structured) esophageal and gastric cancer pathology reports for completeness. Completeness significantly increased from 56% to 97% in the structured reports compared with unstructured narrative reports.…”
Section: Noncore Elementsmentioning
confidence: 99%
“…Completeness significantly increased from 56% to 97% in the structured reports compared with unstructured narrative reports. 83 The ICCR data sets contain all the parameters needed to guide management and prognostication for various cancers. In addition, synoptic reporting may increase awareness of quality indicators, 16 thereby improving the quality of pathologic specimen evaluation.…”
Section: Noncore Elementsmentioning
confidence: 99%